2016
DOI: 10.3748/wjg.v22.i1.435
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic submucosal tunnel dissection for large superficial esophageal squamous cell neoplasms

Abstract: Endoscopic submucosal dissection (ESD) is a well-established treatment for superficial esophageal squamous cell neoplasms (SESCNs) with no risk of lymphatic metastasis. However, for large SESCNs, especially when exceeding two-thirds of the esophageal circumference, conventional ESD is time-consuming and has an increased risk of adverse events. Based on the submucosal tunnel conception, endoscopic submucosal tunnel dissection (ESTD) was first introduced by us to remove large SESCNs, with excellent results. Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 62 publications
1
23
1
Order By: Relevance
“…For this reason, it is especially appropriate for large mucosal lesions[ 11 ]. Zhai et al[ 19 ] obtained similar findings and noted that ESTD is indicated when (1) lesions do not invade deeper than sm1 and have no evidence of lymph node metastasis and (2) the lesion’s circumference level ≥ 1/3 or the diameter ≥ 2 cm.…”
Section: Discussionmentioning
confidence: 79%
“…For this reason, it is especially appropriate for large mucosal lesions[ 11 ]. Zhai et al[ 19 ] obtained similar findings and noted that ESTD is indicated when (1) lesions do not invade deeper than sm1 and have no evidence of lymph node metastasis and (2) the lesion’s circumference level ≥ 1/3 or the diameter ≥ 2 cm.…”
Section: Discussionmentioning
confidence: 79%
“…Postoperative ES is of most concern for large mucosal defects after ESTD because of reduced quality of life. The size of the lesion and histological depth may be reliable predictors of postoperative stricture [10]. In order to reduce the incidence of postoperative stricture, some scholars have reported different methods for the treatment and prevention of ES after ESD or ESTD, such as oral and local injection/administration of steroids, postoperative placement of retrievable metal stents in the esophagus, transplantation of the oral mucosal epithelium, and injection of mesenchymal stem cells [31].…”
Section: Discussionmentioning
confidence: 99%
“…Inspired by the reported success of the submucosal tunnel endoscopic method, endoscopic submucosal tunnel dissection (ESTD) was developed as an alternative technique for the treatment of esophageal neoplastic lesions, especially circumferential superficial esophageal neoplastic lesions (SENLs) [10]. A number of singlecenter studies have reported promising outcomes with the clinical application of ESTD [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…ESTD is indicted for lesions >20 mm in diameter and involving at least one third of the esophageal circumference. 20 A propensity matching analysis by Huang et al 18 demonstrated ESTD significantly shortened the ESD procedural time (38.0 minutes vs 48.0 minutes, p=0.006) and the submucosal dissection time (30.0 minutes vs 40.0 minutes, p=0.005) compared with conventional ESD. In addition, ESTD reduced the rate of muscular injury, although there was no statistical difference in the adverse events.…”
Section: Esophagusmentioning
confidence: 99%